Chemistry for the biosciences : the essential concepts - Crowe, Jonathan (Science writer) (Oxford University Press, 2010)
"Chemistry for the Biosciences leads students through the essential concepts that are central to understanding biological systems, using everyday examples and analogies to build their confidence in an often daunting subject. Placing an emphasis on clear, straightforward explanations, it fosters understanding as opposed to rote learning; by using relevant biological examples throughout, it illustrates just how integral chemistry is to the biosciences."--Pub. desc